1992
DOI: 10.1590/s0074-02761992000500051
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection of wild rodents by Schistosoma mansoni parasitological aspects

Abstract: The evaluation of the role of rodents as natural hosts of Schistosoma mansoni was studied at the Pamparrão Valley, Sumidouro, RJ, with monthly captures and examination of the animals. Twenty-three Nectomys squamipes and 9 Akodom arviculoides with a shistosomal infection rate of 56.5% and 22.2% respectively eliminated a great majority of viable eggs. With a strain isolated from one of the naturally infected N. squamipes, we infected 75% of simpatric Biomphalaria glabrata and 100% of albino Mus musculus mice. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…Although no statistically significant, sex-ratio was male biased, as previously reported in either naturally infected N. squamipes trapped in Sumidouro (Silva et al 1992) or C3H mice infected with isolates derived from Vale do Rio Paraíba do Sul, São Paulo, Brasil) (Bastos et al 1979). The normal adult worm sex-ratio in Brazil is male biased (Souza et al 1996).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Although no statistically significant, sex-ratio was male biased, as previously reported in either naturally infected N. squamipes trapped in Sumidouro (Silva et al 1992) or C3H mice infected with isolates derived from Vale do Rio Paraíba do Sul, São Paulo, Brasil) (Bastos et al 1979). The normal adult worm sex-ratio in Brazil is male biased (Souza et al 1996).…”
Section: Discussionsupporting
confidence: 67%
“…Considerable information acquired from earlier studies carried out at Sumidouro (state of Rio de Janeiro) showed that in a same transmission area, either humans or rodents harbor schistosomiasis mansoni infection (Silva et al 1992). Recently, it was demonstrated that cercariae deriving from sympatric murine and human isolates display only slight differences (Freire et al 2002).…”
mentioning
confidence: 99%
“…These two species also coparasitize their human hosts in Africa. In a locality of Bahia, Brazil, 47% of wild rodents are infected with S. mansoni (36), a favorable situation for interspecies crosses between S. mansoni and rodent schistosomes like Schistosomatium douthitti.…”
Section: Discussionmentioning
confidence: 99%
“…Schistosoma mansoni has been found in many endemic areas in Brazil naturally infecting wild animals (MODENA et al, 2008;MALDONADO et al, 2006). Nectomys squamipes, which is the main non-human definitive host of S. mansoni in Brazil (D'ANDREA et al, 2000), is characterized by its semi-aquatic habits and wide geographic distribution (BONVICINO et al, 2008;MALDONADO et al, 1994;RODRIGUES-SILVA et al, 1992;REY, 1993). Therefore, the occurrence of this semi-aquatic rodent in endemic areas is a factor that makes it difficult to control this zoonosis (SOUZA et al, 1992;D'ANDREA et al, 2000;GENTILE et al, 2006).…”
Section: Introductionmentioning
confidence: 99%